2010
DOI: 10.1111/j.1365-294x.2010.04712.x
|View full text |Cite
|
Sign up to set email alerts
|

The change in genetic diversity down the core‐edge gradient in the eastern spadefoot toad (Pelobates syriacus)

Abstract: Several hypotheses are available to predict change in genetic diversity when approaching peripheral populations. We used the eastern spadefoot toad in Israel as a model system to examine these hypotheses using population genetics analyses and network theory. Our results contradicted most of the predictions from the 'abundant centre' model, that edge populations should have lower density and lower genetic diversity than core populations. Furthermore, dispersal rate between core and peripheral populations is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 62 publications
5
68
1
Order By: Relevance
“…According to the results of the present study, the selection and adaptation to ecological conditions is not done according to the aquatic phase of Spadefoot toads but following metamorphosis. This hypothesis, which is supported by relatively many studies on the conditions of larvae growth of Spadefoot toads [14], shows that the water analysis of larvae is suitable for other amphibians in Israel, and that the distribution of Spadefoot toads is in drier conditions [21]. The burrowing behavior of metamorphosed Spadefoot toads preventing dehydration, as was found in the present study, is very important adaptation to terrestrial life.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…According to the results of the present study, the selection and adaptation to ecological conditions is not done according to the aquatic phase of Spadefoot toads but following metamorphosis. This hypothesis, which is supported by relatively many studies on the conditions of larvae growth of Spadefoot toads [14], shows that the water analysis of larvae is suitable for other amphibians in Israel, and that the distribution of Spadefoot toads is in drier conditions [21]. The burrowing behavior of metamorphosed Spadefoot toads preventing dehydration, as was found in the present study, is very important adaptation to terrestrial life.…”
Section: Discussionsupporting
confidence: 74%
“…The genetic variation among their populations was studied in the southern area of the Mediterranean shoreline [11] [12]. Nevo [13] suggested that Pelobates was best explained by the environmental variability model based on selection for homozygosity as an adaptive strategy in the relatively constant and narrow subterranean niche.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is well recognised in peripheral populations as compared with central ones (the 'central-marginal' genetic pattern) (reviewed in Eckert et al 2008; but see, e.g. Munwes et al 2010). According to the theoretical predictions, less genetically diverse populations are often characterised by lower viability (Frankham 2003;Reed and Frankham 2003;Aguilar et al 2008) and/or adaptability (Young et al 1996, Willi et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…This study supports the hypothesis that various ecological conditions in a relatively small area have little effect on genetic variations, but relatively greater molecular variations were found at greater distances, e.g., in comparison with populations from different countries. Comparisons with other species in Israel showed that Salamandra infraimmaculata (Goldberg et al 2009a), Triturus vittatus vittatus Degani 2007, 2008;Pearlson et al 2010), and Pelobates syriacus (Munwes et al 2010) were more stable and did not have as high a migration rate as was found in P. viridis that used different winter pools (Degani and Kaplan 1999).…”
Section: Discussionmentioning
confidence: 99%